HSP90-CDC37-PP5 forms a structural platform for kinase dephosphorylation - Jasmeen Oberoi; Xavi Aran Guiu; Emily A. Outwin; Pascale Schellenberger; Theodoros I. Roumeliotis; Jyoti S. Choudhary; Laurence H. Pearl (Nature Communications, 2022)
Binding to HSP90-CDC37 is essential for the activity of many protein kinases, but its function is unclear. Here, the authors show that HSP90-CDC37 provides a structural platform for the phosphatase PP5 to dephosphorylate a bound kinase, ‘factory resetting’ it prior to release.